A vanA vancomycin-resistant Enterococcus faecium ST80 outbreak resulting from a single importation event. (29th October 2021) - Pratama, Ryanbi; Beukers, Alicia G; McIver, Christopher J; Keighley, Caitlin L; Taylor, Peter C; van Hal, Sebastiaan J
Abstract: Background: A marked genotype shift among vancomycin-resistant Enterococcus faecium (VREfm) from vanB to vanA in Australia between 2011 and 2015 is a well-known phenomenon. It is hypothesized that this was caused by multiple independent clones emerging simultaneously in different settings and/or regions. Objectives: To gain insights into the circumstances surrounding the shift from vanB to vanA VREfm in one Australian hospital. Methods: The genomes of 69 vanA VREfm isolates from St George Hospital collected between 2009 and 2018 were studied. An expansion of ST80 vanA VREfm was noted following a single introduction. ST80 isolates were thus further characterized using hybrid sequencing and contextualized through comparisons with other published Australian ST80 isolates. Phylogenies were constructed with plasmid sequences compared with the index isolate. Results: The 2011 expansion of ST80 vanA VREfm isolates in our institution originated from the 2009 index isolate, from a patient transferred from overseas. Phylogenetic analysis with other Australian ST80 vanA VREfm isolates showed that the 2011 expansion event was unique, with limited spread to adjacent local health districts. Plasmid analysis showed multiple variants, which can also be traced back to the 2009 isolate, consistent with ongoing plasmid adaptation over time. Conclusions: These findings confirm an expansion event following a VREfm introduction event leading to a sustained clonal and plasmid outbreak over several years. Moreover, it demonstrates the complexity of countrywide replacement events. This study also highlights the use of hybrid sequencing in establishing an epidemiological relationship to the index isolate that was initially inapparent.